YOGA ASANA DALAM MENGEMBANGKAN KECERDASAN JAMAK (MULTIPLE INTELLIGANCES) PADA ANAK DI PENDIDIKAN ANAK USIA DINI PELANGI CAKRANEGARA - Astrina, Wayan Ayumita (Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, 2019)
Early childhood education becomes very important to prepare children to achieve success in the future. Recent research in the field of psychology shows that the future success of children is not only determined by IQ but influenced by other intelligence. Therefore, plural intelligences termed multiple intelligences need to be developed in children from an early age through various learning activities. As in PAUD Pelangi Cakranegara, the development of plural intelligence becomes the main thing especially with the various demands of parents for their children later achievement when entering the school level. Development of multiple intelligence in PAUD Cakranegara done with various learning activities one of them yoga asana practice. In general, yoga asana is known as a system of physical exercise that aims to improve physical and spiritual health. Referring to the background, then conducted a reserch related to the development of multiple intelligences through yoga asana in PAUD Pelangi Cakranegara so that it can be known type of yoga asana is taught and developed intelligence, the process of implementation, and its implications on the child. This research was conducted by using qualitative method with descriptive qualitative data analysis. Data obtained from observation, interview, documentation and checking the validity of data that is: credibility, dependability, and konfirmability. In this research using Humanistic theory and Model theory (Modeling). The results of this study indicate that all asanas trained in PAUD Pelangi Cakranegara can develop multiple intelligences, depending on how the teacher's creativity in conveying the asana movements. This is seen in terms of naming the movement of the names of animals, plants, and other objects, as well as the delivery of the benefits of movement by using a very simple language. From yoga asana practice can develop six multiple intelligences, namely: (1) linguistic intelligences, (2) bodily kinesthetic intelligences, (3) intrapersonal intelligences, (4) interpersonal intelligence, (5) visual / spatial intelligence, (6) spiritual intelligences.The yoga asana practice is done according to the curriculum 2013with integrative thematic. The process of training that includes preparation, integrated implementation, centered on learners, playing while learning, flexible, and evaluation as a result of learning. Implementation of asana yoga practice without any coercion, pressure, but gives freedom, comfort in moving. This yoga asana practice has implications for children's learning readiness and the motivation of children coming to school.